2018
DOI: 10.2174/1389200219666180108160046
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual Variability in Activity of the Major Drug Metabolizing Enzymes in Liver Homogenates of 20 Individuals

Abstract: While hepatic NQO1 activity was highly variable, NQO2 activity was more conserved. In addition, we found that of the hepatic GST isoforms, the variation in GSTM3 levels, which is poorly studied, was highest. The majority of significant correlations were found amongst CYP and UGT enzyme activities. The dataset presented provides the absolute quantification of the largest number of hepatic DME activities so far and constitute an essential resource for in silico toxicokinetic and metabolic modelling studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…Such new platforms are especially needed in biomedical research, as liver damage is a primary cause for post-marketing withdrawal of new drugs, [41] a situation accentuated by the fact that current animal and cell culture models are insufficient to fully predict human physiology or donor-dependent responses. [42,43] The performance of liver organoids within the selected hydrogel upon bioprinting via VBP was investigated. Given the inherent challenge in replicating the multifaceted biosynthetic functions of native hepatocytes in vitro, we specifically analyzed i) the viability of the printed structures, and ii) the influence of the VBP on organoid microstructure and morphology, as a preliminary step to promote the differentiation and maturation capacity of the printed construct into hepatic-like structures.…”
Section: Resultsmentioning
confidence: 99%
“…Such new platforms are especially needed in biomedical research, as liver damage is a primary cause for post-marketing withdrawal of new drugs, [41] a situation accentuated by the fact that current animal and cell culture models are insufficient to fully predict human physiology or donor-dependent responses. [42,43] The performance of liver organoids within the selected hydrogel upon bioprinting via VBP was investigated. Given the inherent challenge in replicating the multifaceted biosynthetic functions of native hepatocytes in vitro, we specifically analyzed i) the viability of the printed structures, and ii) the influence of the VBP on organoid microstructure and morphology, as a preliminary step to promote the differentiation and maturation capacity of the printed construct into hepatic-like structures.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, primary human hepatocytes (pHHs) are the "gold standard" for in vitro studies on hepatic metabolism, clearance, hepatotoxicity and drug-drug interaction [9]. However, this research is still restricted by pHH scarcity, donor variability and their rapid dedifferentiation in vitro [10][11][12][13][14]. An inflammatory response by endotoxin contamination [15,16] originating from bacterial collagenase preparations, loss of normal cell polarity when dissolving them from liver tissue or down-regulation of liver-specific transcription factors influencing phase I/II protein expression were discussed as possible causes [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that fecal GUS difference across individuals is significant (4~6 folds). Although microbial GUS activity is highly different across individual rats, this variation did not exceed the individual variations of phase I and II enzymes (e.g., CYPs and UGTs) activities [ 38 , 39 ]. In order to determine precision activity, researchers should pay more attention towards individual variation as it has never been reported in literature.…”
Section: Discussionmentioning
confidence: 99%